Responsibility for Ensuring Safety and Security in Local Environment: Opinions of Those Responsible in Slovenian Municipalities - Dvojmoč, Miha (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Researchers and practitioners in the field of security are aware that safety is not solely the responsibility of the state and that ensuring it requires cooperation between the government, local authorities, municipal wardens, companies, individuals, NGOs, and sometimes even citizens. The responsibility of local self-government for the pluralization of security provisions varies depending on the context and jurisdiction. Generally, local authorities are responsible for public safety and protection, which includes maintaining order and promoting security initiatives. Policing services in local communities are provided by both national and local police (municipal police, inspection services) and various stakeholders of plural policing activities. This paper presents the results of a study conducted on a sample of 61 individuals responsible for security in Slovenian municipalities. They assessed the importance of different institutions for ensuring security and the level of development of safety programs in the local environment.